Measurement of Calcium Dissociation Rates from Troponin C in Rigor Skeletal Myofibrils - Little, Sean C.; Tikunova, Svetlana B.; Swartz, Darl R.; Norman, Catalina; Davis, Jonathan P. (Frontiers in Physiology, 2011)
Ca2+ dissociation from the regulatory domain of troponin C may influence the rate of striated muscle relaxation. However, Ca2+ dissociation from troponin C has not been measured within the geometric and stoichiometric constraints of the muscle fiber. Here we report the rates of Ca2+ dissociation from the N-terminal regulatory and C-terminal structural domains of fluorescent troponin C constructs reconstituted into rabbit rigor psoas myofibrils using stopped-flow technology. Chicken skeletal troponin C fluorescently labeled at Cys 101, troponin C-IAEDANS, reported Ca2+ dissociation exclusively from the structural domain of troponin C at 0.37, 0.06 and 0.07/s in isolation, in the presence of troponin I and in myofibrils at 15oC, respectively. Ca2+ dissociation from the regulatory domain was observed utilizing fluorescently labeled troponin C containing the T54C and C101S mutations. Troponin reported Ca2+ dissociation exclusively from the regulatory domain of troponin C at >1000, 8.8 and 15/s in isolation, in the presence of troponin I and in myofibrils at 15oC, respectively. Interestingly, troponin reported a biphasic fluorescence change upon Ca2+ dissociation from the N and C-terminal domains of troponin C with rates that were similar to those reported by troponin and troponin C-IAEDANS at all levels of the troponin C systems. Furthermore, the rate of Ca2+ dissociation from troponin C in the myofibrils was similar to the rate of Ca2+ dissociation measured from the troponin C-troponin I complexes. Since the rate of Ca2+ dissociation from the regulatory domain of TnC in myofibrils is similar to the rate of skeletal muscle relaxation, Ca2+ dissociation from troponin C may influence relaxation.